2017
DOI: 10.1016/j.earscirev.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

River temperature modelling: A review of process-based approaches and future directions

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
110
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(131 citation statements)
references
References 145 publications
1
110
0
Order By: Relevance
“…Previous data limitations have not constrained the number of studies that address temperatures in lotic systems, which is a popular topic with reviews common in both the physical science (Webb et al 2008; Gallice et al 2015; Dugdale et al 2017) and ecological literatures (Ward 1985; Poole and Berman 2001; Caissie 2006; Olden and Naiman 2010; Steel et al 2017). By necessity, however, a primary focus has often been the description and modeling of thermal characteristics at a small number of sites or across areas of limited geographic extent.…”
Section: Introductionmentioning
confidence: 99%
“…Previous data limitations have not constrained the number of studies that address temperatures in lotic systems, which is a popular topic with reviews common in both the physical science (Webb et al 2008; Gallice et al 2015; Dugdale et al 2017) and ecological literatures (Ward 1985; Poole and Berman 2001; Caissie 2006; Olden and Naiman 2010; Steel et al 2017). By necessity, however, a primary focus has often been the description and modeling of thermal characteristics at a small number of sites or across areas of limited geographic extent.…”
Section: Introductionmentioning
confidence: 99%
“…Water temperatures exert a primary control on river ecosystem function with influences on habitat suitability (e.g., Boisneau et al, ) and growth rates (e.g., Deegan et al, ; Nicieza & Metcalfe, ) for aquatic species, as well as physical (Arp et al, ; Merck & Neilson, ; Pohl et al, ; Rawlins et al, ; Syvitski, ) and chemical (Cory et al, ; McNamara et al, ) river processes. Given the ecological importance of river temperature, understanding the controlling heat fluxes is key to effective river management (Dugdale et al, ; Hannah & Garner, ; Poole & Berman, ). This can be even more important in a changing climate where energy balances can shift (Caldwell et al, ; Luce et al, ; Muñoz‐Mas et al, ; van Vliet et al, ) and has already been shown to impact some rivers (e.g., Isaak et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Stream temperature is an aggregate of conductive, convective and advective fluxes between water column, stream bed, hyporheic zone, groundwater, seeps of varying origin, shade and substrate type (Webb and Zhang 1997;Johnson 2004;Guenther et al 2014;Fullerton et al 2015). The dominant process influencing stream temperature is solar loading (Brown 1969;Torgersen et al 2001;Mayer 2012;Dugdale et al 2017;Dugdale et al 2018;Loicq et al 2018). A barrier to solar loading such as riparian vegetation or topographic shading reduces stream temperature (Bond et al 2015;Kalny et al 2017;Wawrzyniak et al 2017).…”
Section: Hydroclimate Impacts From Fog and Low Cloudsmentioning
confidence: 99%